Cutaneous necrosis secondary to subcutaneous extravasation of acyclovir - Imane Couissi; Zakia Douhi; Kawtar El Fid; Meryem Soughi; Sara El Loudi; Hanane BayBay; Fatima Zahra Mernissi (Our Dermatology Online, 2023)
Subcutaneous extravasation of infused vesicant solutions is becoming a common problem in medical practice, and can result in severe and progressive tissue dysfunction, ranging from persistent tissue edema to tissue necrosis. Although Acyclovir is a known vesicant drug, responsible for venous and soft tissue irritation, they are a few reported cases of extravasation of Aciclovir. We report here the 5th case of Subcutaneous extravasation of intravenous (IV) acyclovir in a patient hospitalized for herpes zoster cruris, causing skin necrosis on day 4 of her hospitalization and leaving a residual scar. Early recognition of extravasation and prompt management are essential to prevent additional morbidity and optimize outcomes.